2018
DOI: 10.1055/a-0630-1529
|View full text |Cite
|
Sign up to set email alerts
|

Relation of RANKL and OPG Levels with Bone Resorption in Patients with Acromegaly and Prolactinoma

Abstract: The objective of this study was to investigate the effect of hyperprolactinemia and high levels of insulin-like growth factor-I (IGF-I) on bone resorption and their relation with receptor activator of nuclear factor-κB ligand (RANKL) and osteoprotegerin (OPG) in patients with prolactinoma and acromegaly. Thirty-one patients with acromegaly, 28 patients with prolactinoma, and 33 healthy individuals were included in the study. Serum concentrations of RANKL, OPG, bone alkaline phosphatase (bone ALP), osteocalcin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 18 publications
(21 reference statements)
0
9
1
Order By: Relevance
“…PRL within the physiological range stimulates bone formation, mild hyperprolactinaemia increases bone resorption, and marked hyperprolactinaemia further increases bone resorption and inhibits bone formation [77]. This is supported by findings that patients with prolactinoma have suppressed osteocalcin, high NTX (collagen type I crosslinked N-telopeptide), and increased RANKL (receptor activator of nuclear factor-kB ligand)/OPG (osteoprotegerin) ratio, suggesting increased bone resorption and decreased bone formation [77,78]. The relative contribution of hypogonadotropic hypogonadism and hyperprolactinemia is controversial and it has been hypothesized that these mechanisms have synergistic effects on bone loss [77].…”
Section: Bone Manifestationsmentioning
confidence: 86%
“…PRL within the physiological range stimulates bone formation, mild hyperprolactinaemia increases bone resorption, and marked hyperprolactinaemia further increases bone resorption and inhibits bone formation [77]. This is supported by findings that patients with prolactinoma have suppressed osteocalcin, high NTX (collagen type I crosslinked N-telopeptide), and increased RANKL (receptor activator of nuclear factor-kB ligand)/OPG (osteoprotegerin) ratio, suggesting increased bone resorption and decreased bone formation [77,78]. The relative contribution of hypogonadotropic hypogonadism and hyperprolactinemia is controversial and it has been hypothesized that these mechanisms have synergistic effects on bone loss [77].…”
Section: Bone Manifestationsmentioning
confidence: 86%
“…The increased bone turnover is directly related to the levels of circulating GH and IGF-I (40). The increased bone remodeling is likely due to the actions of IGF-I on the induction of RANKL leading to enhanced osteoclastogenesis (40,72,73). Analyzing gene expression in sphenoid bone tissue samples of subjects with acromegaly, Belaya et al suggested that GH excess may induce mesenchymal stem cell commitment toward cartilage or adipocytes instead of toward mature osteoblasts (74).…”
Section: Effects Of Gh Excess On Bone Formation and Resorptionmentioning
confidence: 99%
“…Hyperprolactinemia per se or through hypogonadism induces an increased bone turnover, with a predominance of bone resorption and, consequently, an increased occurrence of osteopenia and osteoporosis ( 11 , 36 , 37 , 38 ). Suppressed levels of osteocalcin (OC), high collagen type I crosslinked N-telopeptide (NTX), and increased receptor activator of nuclear factor-kB ligand (RANKL)/osteoprotegerin ratio have been reported in patients with prolactinoma ( 39 , 40 ). Both in females and in males, trabecular bone in the spine and in the hip is more affected than cortical bone in the distal radium; in fact, spinal bone mineral content is generally reduced from 20 to 30% and forearm bone mineral content from 2.5 to 10% ( 41 ).…”
Section: Clinical Issuesmentioning
confidence: 99%